(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Investigations about biochemical composition and nutritional value of snail meat are few. Research was conducted on flesh flour from snail (Limicolaria flammea) collected in Agboville (South, Côte d’Ivoire). The proximate composition showed that snail (Limicolaria flammea) flesh flour was rich in protein (46.65±0.05 %) and low in fat (8.64±0.6 %), total carbohydrate (8.20±0.01 %) , total sugars (7.8±0.25 %) reducing sugars (7.23±0.04 %) and ash (6.23±0.01 %). The major minerals were phosphorus (3365.33±0.33 mg/Kg), calcium (1654.54±0.06 mg/Kg) potassium (1324.54± 4.18 mg/Kg) and sodium (668.69±1.13 mg/Kg). The major vitamins were vitamin B9 (21.56±0.17 µg/100g), vitamin C (18.34±1.30 µg/100g) and vitamin E (18.12±2.1 µg/100g). The chromatographic profile of amino acids revealed fifteen amino acids of which five are the dominant ones. Those are lysine (2.38±0.01 mg/100g), valine (1.45±0.02 mg/100g), methionine (1.26±0.03 mg/100g), isoleucine (1.24±0.01 mg/100g), leucine (1.05±0.01 mg/100g), the others have contents lower than 1mg /100g. Oxalate and phytate anti-nutritional parameters are non-existent in flour and tannins content was 0.18±0.01 mg/100g.